2016
DOI: 10.22211/cejem/64967
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Explosion of Aluminized Explosives in Air

et al.

Abstract: Piezoelectric gauges were used to measure the shock wave overpressure of aluminized explosives and of a TNT charge. An infrared thermal-imaging spectrometer was used to collect the infrared signatures produced by the explosion fireball when the examined explosives were detonated. The measurement of the infrared signatures was used to estimate the surface temperatures and the dimensions of the fireball. Two aluminized explosive compositions (RDX/Al/AP and RDX/Al/B/AP) have been analyzed. 500 g charges of the al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…(1), the relative charge mass by considering the peak overpressure generated by the TBX charges could be calculated, and the value is 2.35 kg. The TNT equivalent of TBX based on the overpressure can be determined from the following equation [19]: trueq=Meq/M …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1), the relative charge mass by considering the peak overpressure generated by the TBX charges could be calculated, and the value is 2.35 kg. The TNT equivalent of TBX based on the overpressure can be determined from the following equation [19]: trueq=Meq/M …”
Section: Resultsmentioning
confidence: 99%
“…They also analyzed the shock wave propagation and quasi‐static pressure effect of the pressed TBX with different particle size in an open space and steel chambers. When a 500 g pressed aluminized explosive is detonated, the highest surface temperature of fireball could reach 1600 °C, which was much higher than that of TNT and the duration time of temperature above 700 °C was 2.73 times longer than that of TNT [19]. Simić et al.…”
Section: Introductionmentioning
confidence: 99%
“…A slow cook-off test was performed to study the thermal performance of PBFMO-b-PNMMO and Al powders. [33][34][35] The cook-off curves of thermoplastic elastomers/Al compositions (Fig. 10) show an initial linear curves, subsequent impetuous curves and ultimately linear curves again.…”
Section: Cook-off Testmentioning
confidence: 99%
“…Y. Chen et al. [9] found that the aluminized explosive with boron powders had higher values in shock wave over‐pressure, surface temperature and duration of explosion fireballs than TNT and aluminized explosive without boron powders. E. C. Koch et al.…”
Section: Introductionmentioning
confidence: 99%
“…M. N. Makhov et al [8] showed that the addition of aluminum powder and boron powder remarkably increased the explosion heat of explosives. Y. Chen et al [9] found that the aluminized explosive with boron powders had higher values in shock wave over-pressure, surface temperature and duration of explosion fireballs than TNT and aluminized explosive with-out boron powders. E. C. Koch et al [10] studied the detonation velocities and pressures of the boron-based high explosives, and discovered that the detonation velocities of the boron-based compounds were always higher than that of the corresponding carbon-based compounds.…”
Section: Introductionmentioning
confidence: 99%